Aortitis as a Harbinger of Occult Malignancy - Erik W. O’Connell; Jennifer Reams; Alfred E. Denio (Case Reports in Rheumatology)
Noninfectious aortitis can be associated with an occult malignancy. Although glucocorticosteroids are often used, there is no clear evidence-based therapy and there is little consensus regarding treatment. Identifying and treating an underlying trigger is the most efficacious therapy. We present an unusual case initially concerning acute bacterial endocarditis of the native mitral valve; however, aseptic ischemic valvitis manifested on pathology. Concurrent aortitis was diagnosed with angiography. Occult colon adenocarcinoma was discovered during diagnostic abdominal imaging. Treatment of this underlying malignancy was associated with dynamic mitigation of inflammation affecting the entire aorta and a reduction in associated symptoms. This is an unusual case of a paraneoplastic secondary large vessel vasculitis involving the entire aorta, a diagnosis of exclusion but a consideration that can have dramatic impact on both morbidity and mortality.